Personality disorders and suicide attempts - Muquebil Ali Al Shaban Rodriguez, O.W.; López Fernández, J.R.; Huergo Lora, C.; Ocio León, S.; Hernández González, M.J.; Alonso Huerta, A.; Gómez Simón, M.; Abad Acevedo, I.; Rubio Rodríguez, L.; García Álvarez, G.; González Suárez, A. (European psychiatry, 2016)
The personality disorders are defined according to the DSM-5 like “an enduring maladaptive patterns of behavior, cognition and inner experience, exhibited across many contexts and deviating markedly from those accepted by the individual's cultures. These patterns develop in adolescence and the beginning of adulthood, and are associated with significant distress or disability”. The personality disorders can be a risk factor for different processes of the psychiatric pathology like suicide. The personality disorders are classified in 3 groups according to the DSM-5: – cluster A (strange subjects): paranoid, schizoid and schizotypal; – cluster B (immature subjects): antisocial, bordeline, histrionic and narcissistic; – cluster C (frightened subjects): avoidant, dependent and obsessive-compulsive. To describe the influence of personality disorders in suicide attempts. Exhibition of clinical cases. In this case report, we exhibit three clinical cases of suicide attempts which correspond to a type of personality disorder belonging to each of the three big groups of the DSM-5 classification, specifically the paranoid disorder of the cluster A, the disorder borderline of cluster B and the obsessive compulsive of cluster C. The personality disorders have a clear relation with the suicide attempts, increasing this influence in some of them, especially the borderline personality disorder.